1999
DOI: 10.1162/089892999563526
|View full text |Cite
|
Sign up to set email alerts
|

Short-and Long-Delay Intracranial ERP Repetition Effects Dissociate Memory Systems in the Human Brain

Abstract: Prior exposure to a stimulus can facilitate the performance to subsequent presentations of that stimulus. ERP studies have shown that this facilitation is associated with the modulation of two components (N400 and P600). Investigation of the time course of both behavioral and ERP repetition effects have led to the assumption that it is subserved by the combination of at least two mechanisms operating at different time-points: a short-delay semantic activation and a long-lasting episodic mechanism. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
0
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 91 publications
(116 reference statements)
11
53
0
1
Order By: Relevance
“…This modulation relative to the processing of relevant and interactive information has been already described [14]. ERP recordings of patients with frontal lesions have provided evidence of an orbital and ventral medial origin for this ERP component [31]. Our results are thus in line with the idea that the orbital and dorsolateral regions of the frontal lobe are involved in processing target specifications [23,34] or in maintaining new information in memory during interference [17,56].…”
Section: Frontal N250: Strategic Demands and Processing Contextsupporting
confidence: 89%
“…This modulation relative to the processing of relevant and interactive information has been already described [14]. ERP recordings of patients with frontal lesions have provided evidence of an orbital and ventral medial origin for this ERP component [31]. Our results are thus in line with the idea that the orbital and dorsolateral regions of the frontal lobe are involved in processing target specifications [23,34] or in maintaining new information in memory during interference [17,56].…”
Section: Frontal N250: Strategic Demands and Processing Contextsupporting
confidence: 89%
“…Depth recordings in several paralimbic and association neocortical regions have shown N400-P600 potentials (Guillem et al, 1999;Halgren et al, 1994), which suggest a very intimate relationship and possible interdependency between these two late components. Guillem et al (1999), however, found that N400 repetition effects, unlike P600 repetition effects, were generally only present in the neocortex when shorter inter-item lags (~ 25 s) were used in a visual recognition memory task.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that the loss of the P600 word repetition effect in AD is a reflection of a functional disconnection between mesial temporal and cortical (e.g. orbitofrontal, temporal pole, middle temporal gyrus) P600 generators, several of which have convergent reciprocal connections with the parahippocampal gyrus (Buzsáki, 1996;Guillem et al, 1999;Traub and Miles, 1991). As patients progress into the advanced stages of AD (Braak stages V and VI), a more global disturbance of neocortical function develops, which can be quantified by electrophysiological measures such as the N400, P600 or P300 components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research was focused on the signal's time period between 500 and 800 msec after the presentation of the warning stimulus. This time period corresponds to the P600 ERP component, as mentioned above, which is accepted as reflecting the completion of any synchronized operations, concerning a decision taken after the presentation of a warning stimulus and the target detection [8][9] [23]. Specifically, its amplitude is considered as an index of the cost of processing, while its latency as a function of the onset and duration of processes [9].…”
Section: Discussionmentioning
confidence: 99%